Presidential Decree-law No. 100 of the Year 2015 On Amending Some Provisions of the Penal Code = قرار رئيس جمهورية مصر العربية بالقانون رقم 100 لسنة 2015 بتعديل بعض أحكام قانون العقوبات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic